Community-Based Eco-Tourism Development Strategies in Damaran Baru Village, Bener Meriah Regency: Opportunities and Challenges - Hajad, Vellayati; Fadhly, Zuhrizal; Husna, Cut Asmaul; Harakan, Ahmad; Ikhsan, Ikhsan (Universitas Muhammadiyah Tangerang, 2025)
The increasing tourism activity raises concerns about environmental impacts and sustainability. Sustainable ecotourism must utilize natural and cultural attractions to create tourism experiences that generate economic benefits and prioritize environmental conservation and social welfare. The Bener Meriah Regency Government of Aceh has implemented policies to encourage eco-villagebased tourism. This study uses a qualitative research method with a phenomenological approach. Data collection was carried out through observation, direct interviews, and document studies. The results of the study indicate that Damaran Baru Village in Bener Meriah Regency is an example of the success of an environmentally based eco-village. In addition, the government also plays an important role in encouraging sustainable tourism practices that are beneficial to the environment and community welfare. The gap in this research lies in the lack of in-depth exploration of the implementation of eco-villages, especially in Damaran Baru Village, Bener Meriah Regency, Aceh. Although there have been many studies discussing sustainable tourism, only a few highlight the active role of the government in encouraging the development of eco-villagebased tourism. The novelty of this study lies in the presentation of a concrete case study of the success of an eco-village in Damaran Baru Village that combines environmental conservation with local economic development. So, economic growth can go hand in hand through the development of eco-villages. Recommendations for the development of Damaran Baru eco-village are improving tourism infrastructure, providing ongoing training to the community, diversifying sources of income, and collaborating with external parties.Meningkatnya aktivitas pariwisata menimbulkan kekhawatiran terhadap dampak lingkungan dan keberlanjutan. Ekowisata berkelanjutan harus memanfaatkan daya tarik alam dan budaya untuk menciptakan pengalaman wisata yang menghasilkan manfaat ekonomi dan mengedepankan pelestarian lingkungan dan kesejahteraan sosial. Pemerintah Kabupaten Bener Meriah Aceh telah menerapkan kebijakan untuk mendorong pariwisata berbasis eco-village. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan fenomenologis. Pengumpulan data dilakukan melalui observasi, wawancara langsung, dan studi dokumen. Hasil penelitian menunjukkan bahwa Desa Damaran Baru di Kabupaten Bener Meriah merupakan contoh keberhasilan eco-village berbasis lingkungan. Selain itu, pemerintah juga berperan penting dalam mendorong praktik pariwisata berkelanjutan yang bermanfaat bagi lingkungan dan kesejahteraan masyarakat. Kesenjangan penelitian ini terletak pada kurangnya eksplorasi mendalam terhadap implementasi eco-village, khususnya di Desa Damaran Baru, Kabupaten Bener Meriah, Aceh. Meskipun sudah banyak penelitian yang membahas tentang pariwisata berkelanjutan, hanya sedikit yang menyoroti peran aktif pemerintah dalam mendorong pengembangan pariwisata berbasis eco-village. Kebaruan penelitian ini terletak pada penyajian studi kasus konkret tentang keberhasilan eco-village di Desa Damaran Baru yang memadukan pelestarian lingkungan dengan pengembangan ekonomi lokal. Jadi, pertumbuhan ekonomi bisa berjalan beriringan melalui pengembangan eco-village. Rekomendasi pengembangan eco-village Damaran Baru adalah perbaikan infrastruktur pariwisata, pemberian pelatihan berkelanjutan kepada masyarakat, diversifikasi sumber pendapatan, dan kerjasama dengan pihak eksternal.